Dose Reduction to Motor Structures in Adjuvant Fractionated Stereotactic Radiotherapy of Brain Metastases: nTMS-Derived DTI-Based Motor Fiber Tracking in Treatment Planning - Diehl, Christian D.; Rosenkranz, Enrike; Schwendner, Maximilian; Misslbeck, Martin; Sollmann, Nico; Ille, Sebastian; Meyer, Bernhard; Combs, Stephanie E.; Krieg, Sandro M. (Cancers, 2023)
Background: Resection of brain metastases (BM) close to motor structures is challenging for treatment. Navigated transcranial magnetic stimulation (nTMS) motor mapping, combined with diffusion tensor imaging (DTI)-based fiber tracking (DTI-FTmot.TMS), is a valuable tool in neurosurgery to preserve motor function. This study aimed to assess the practicability of DTI-FTmot.TMS for local adjuvant radiotherapy (RT) planning of BM. Methods: Presurgically generated DTI-FTmot.TMS-based corticospinal tract (CST) reconstructions (FTmot.TMS) of 24 patients with 25 BM resected during later surgery were incorporated into the RT planning system. Completed fractionated stereotactic intensity-modulated RT (IMRT) plans were retrospectively analyzed and adapted to preserve FTmot.TMS. Results: In regular plans, mean dose (Dmean) of complete FTmot.TMS was 5.2 ± 2.4 Gy. Regarding planning risk volume (PRV-FTTMS) portions outside of the planning target volume (PTV) within the 17.5 Gy (50%) isodose line, the DTI-FTmot.TMS Dmean was significantly reduced by 33.0% (range, 5.9–57.6%) from 23.4 ± 3.3 Gy to 15.9 ± 4.7 Gy (p < 0.001). There was no significant decline in the effective treatment dose, with PTV Dmean 35.6 ± 0.9 Gy vs. 36.0 ± 1.2 Gy (p = 0.063) after adaption. Conclusions: The DTI-FTmot.TMS-based CST reconstructions could be implemented in adjuvant IMRT planning of BM. A significant dose reduction regarding motor structures within critical dose levels seems possible.
CRIS-Team Scopus Importer:2023-03-08
Keywords: brain metastases; fiber tracking; stereotactic fractionated radiotherapy